Understanding Fertility Dynamics and Son Preference in India: A Comprehensive Review - N. Sharat Singh; M. Sanjita Devi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This literature review delves into the complex relationship among fertility patterns, son preference, and socio-cultural dynamics within the Indian context, with a broader exploration of similar themes in developing and least developed countries. Through a comprehensive analysis of recent studies, the review sheds light on the intricate interplay between socio-cultural norms, economic variables, and fertility preferences, highlighting the enduring influence of son preference on reproductive behaviour. Moreover, it examines the implications of son preference on gender disparities in reproductive health outcomes and demographic stability. The review underscores the need for multifaceted interventions, including policy initiatives, community engagement, and socio-cultural transformations, to address the underlying drivers of son preference and promote gender equality and reproductive rights in diverse socio-cultural contexts.